ANALYZING THE IMPACT OF LEADERSHIP STYLE TOWARD ORGANIZATIONAL CHANGE IN PT PINDAD - Fadillah, Fairuz Khansa; Pritasari, Adita (Journal of Business and Management, 2017)
Abstract.Background: There are many studies that identified the relationship between the leadership style and thesuccess of organizational change implementation is significant. In this research, the researcher focus on the real case that happened in PT PINDAD is currently on the process of implementing their new culture. The researcher tried to identify whether the leadership style has a significant relationship with organizational change . Methods: The  organizational  change  recipients’  belief  measured  using  OCRBS,  and  the  leadership  style measured using the Multi-Leadership Questionnaire.Results: The  results  of  this  research  show  that  the  leadership  style  has  significant  impact  on  the organizational change, and both of transformational leadership and transactional leadership give a positiveimpact on the organizational change. The current leadership style that PT PINDAD used is Management-by- exception, while results show that Inspirational Motivation is a leadership style that gives highest positive impact among other seven leadership style on organizational change in PT PINDADConclusion: improving the leadership style will beneficial for PT PINDAD, since there is a significant impactof  leadership  on  organizational  change.  Applied  appropriate  leadership  style  will  help  the  process  of organizational change implementation. Keywords: Leadership Style, Organizational Change, Transactional Leadership, Transformational Leadership